1987
DOI: 10.1002/jcc.540080814
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the relative stabilities of the isomers of CF2N2: Comparison of ab initio and MNDO calculations

Abstract: A b initio SCF calculations at the HF/3-21G level and semi-empirical MNDO calculations have been used to locate the stationary points on the CFzNz energy surface. Perfluorodiazomethane is predicted to be most stable isomer, but perfluorodiazirine is predicted to lie only ca 41 k J higher in energy at the SCF level. There are significant differences between the ab initio and MNDO results for the ordering of some of the isomers. Frequency calculations give results in good agreement with the limited experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…E Diazo compounds and diazirines [316] Stable diazoalkanes and diazirines (Figure 8.120, where X and Y are fluoroalkyl groups) have been isolated, but no authenticated report is available of a diazoalkane where X or Y is a fluorine atom, although difluorodiazirine is now well documented [316]. It has been suggested that this is probably yet another result of the propensity of fluorine to favour the formation of F2Cðsp 3 Þ bonds, rather than F2Cðsp 2 Þ, thus making the diazirine structure thermodynamically preferred, although calculations have suggested that the diazomethane structure is slightly preferred for CF 2 N 2 [317]. Oxidation of fluorinated hydrazones with lead tetra-acetate forms a useful method for the synthesis of bis(perfluoroalkyl)diazomethanes [318] (Figure 8.121 Bis(perfluoroalkyl)diazoalkanes are surprisingly stable; for example, deliberate attempts to detonate 2-diazoperfluoropropane failed [318].…”
Section: Azo Compoundsmentioning
confidence: 99%
“…E Diazo compounds and diazirines [316] Stable diazoalkanes and diazirines (Figure 8.120, where X and Y are fluoroalkyl groups) have been isolated, but no authenticated report is available of a diazoalkane where X or Y is a fluorine atom, although difluorodiazirine is now well documented [316]. It has been suggested that this is probably yet another result of the propensity of fluorine to favour the formation of F2Cðsp 3 Þ bonds, rather than F2Cðsp 2 Þ, thus making the diazirine structure thermodynamically preferred, although calculations have suggested that the diazomethane structure is slightly preferred for CF 2 N 2 [317]. Oxidation of fluorinated hydrazones with lead tetra-acetate forms a useful method for the synthesis of bis(perfluoroalkyl)diazomethanes [318] (Figure 8.121 Bis(perfluoroalkyl)diazoalkanes are surprisingly stable; for example, deliberate attempts to detonate 2-diazoperfluoropropane failed [318].…”
Section: Azo Compoundsmentioning
confidence: 99%